Accounting Uniformity, Comparability, and Resource Allocation Efficiency - Corona, Carlos; Huang, Zeqiong; Hwang, Hyun (The Accounting Review, 2024)
ABSTRACT Uniformity is an essential feature of financial reporting, yet its desirability has long been debated. We study a model in which firms decide whether to adopt either their locally preferred accounting methods or a common method, followed by an investor allocating capital across firms. Firms’ choices of a common method are strategic complements in attaining more comparable reports. As a result, multiple equilibria may exist. Specifically, an equilibrium in which firms use their local methods always exists. However, an equilibrium in which firms adopt a common method exists if uniformity improves comparability significantly and firm-specific productivity shocks are large relative to the common productivity shock. Firms may fail to coordinate on adopting the Pareto-dominant accounting method, which may not even emerge as an equilibrium if investments exhibit substitutability. These coordination problems provide accounting regulation an opportunity to facilitate efficient capital allocation, thus providing a microfoundation for accounting measurement regulation. JEL Classifications: D02; D61; D83; H11; M40; M41; M48.